An extensive structural model of supply chain quality management and firm performance - Huy Truong Quang (2016)
Purpose – The purpose of this paper is to explore the concept of supply chain quality management (SCQM) and to propose a research model that considers the impact of SCQM practices on firm performance. Design/methodology/approach – Based on a comprehensive literature review, SCQM most relevant practices were analyzed and selected. These practices were categorized into four dimensions: upstream (supplier assessment, supplier quality management (QM)), downstream sides of a supply chain (customer focus), internal process (product/service design, process management and logistics) and support practices (top management support, human resource management, information and supply chain integration). The measurement instrument of firm performance was also developed, including three aspects: operational performance, customer satisfaction and financial performance. Findings – An innovative conceptual framework that provides a comprehensive picture covering core dimensions of SCQM and various aspects of firm performance was proposed. This conceptual framework can be used as “a guideline” for theory building and measurement instrument development of SCQM and firm performance. More importantly, on the road to gain a further insight, an extensive structural model that identifies direct and indirect relationships between SCQM and firm performance was also developed. Practitioners/managers can apply this model as “a road map” for implementing SCQM practices. Research limitations/implications – It is necessary to test the rationality of these models by using empirical studies in different contexts. Originality/value – The integration of quality and supply chain management still remains limited in the literature. Therefore, it is necessary to have a more focussed approach in assessing QM issues within the internal and external supply chain contexts. This study concentrates on the practices which improve quality aspects of the supply chain, known as SCQM practices. Proposed research models in this paper not only fill out the voids in the literature, but also contribute with conceptual frameworks for theory building in SCQM and firm performance. The authors also expect that this research can offer a useful guidance for measuring and implementing SCQM practices as well as facilitate further studies in this field.